Adequacy of pseudo-direct georeferencing of terrestrial laser scanning data for coastal landscape surveying against indirect georeferencing. Issue 1 (1st January 2017) - Jaud, Marion; Letortu, Pauline; Augereau, Emmanuel; Le Dantec, Nicolas; Beauverger, Mickaël; Cuq, Véronique; Prunier, Christophe; Le Bivic, Réjanne; Delacourt, Christophe
ABSTRACT: The georeferencing process is crucial to the accuracy of terrestrial laser scanner (TLS) data, in particular in the context of diachronic studies relying on multi-temporal surveys. The use of Ground Control Points in the georeferencing process can however be complex when confronted with the practical constraints of coastal surveying. A simple and quick alternative method called "pseudo-direct georeferencing" is proposed in the present paper. This method involves internal inclinometers to measure roll and pitch angles and a centimetric GPS to measure the position of the TLS center and the position of one backsight target. When assessing the transformational uncertainty by using a set of independent ground validation points for both classical indirect and proposed pseudo-direct methods, we respectively obtain root mean square errors of 4.4 cm for the indirect method and 3.8 cm for the pseudo-direct method.